Majaz Isti'arah Analysis Terms of Mulaim in Arabic Oral Perspective - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2022)
Arabic is a language with a uslub style (grammar) which has a high degree of comparison with other languages. Aesthetics and authenticity in Arabic need to be studied in depth, especially in the discussion of balaghah science, to understand the appropriateness of the intended meaning. Expert of balaghah provides many lughowiyah studies related to the oral of the Arabs. The purpose of connotation or majaz in balaghah science is feared to cause a misunderstanding of the meaning desired by the mutakalim. Therefore, analysis and research to examine sentences with purposes are necessary to assist in directing mustami' or qori' to the intended meaning of mutakalim. This research uses the library method by collecting references from books and journals. The approach used is a qualitative approach with a description of the analysis. Data collection was carried out using balaghah books, then processed and analyzed in stages until they understood each sub-discussion. The results showed that majaz was mainly found in the mouth of the Arabs. Majaz is classified in various forms, one of which is isti'arah majaz based on the mulaim or compatibility between musyabbah and musyabbah bih with qorinah or lafadz after it. There are three kinds of isti'arah based on the mulaim: isti'arah murasysyah, mujarrodah, and muthlaqah.